Correction: Optimization of hydrophobic nanoparticles to better target lipid rafts with molecular dynamics simulations. Issue 30 (28th July 2020) - Lin, Xiaoqian; Lin, Xubo; Gu, Ning
Abstract : Correction for 'Optimization of hydrophobic nanoparticles to better target lipid rafts with molecular dynamics simulations' by Xiaoqian Lin et al., Nanoscale, 2020, 12, 4101–4109, DOI: ; 10.1039/C9NR09226A .